Hopes versus reality - Grouse, Lawrence; Zeng, Guangqiao; Zhong, Nanshan (Journal of Thoracic Disease; Vol 6, No 6 (June 26, 2014): Journal of Thoracic Disease, 2014)
We have noticed the publication of a series of small, shortterm studies using the ketamine for such varied conditions as suicidal ideation in depression (1), post-traumatic stress disorder (2), and treatment-refractory depression (3). These brief and inconclusive reports have been picked up throughout the internet portraying these uses as “a cure for depression” and “promising therapy for mental illness.” Stories about these preliminary findings have been published with an uncritical eye in such large global internet portals as Huffington Post (4), National Public Radio (5), and CBS (6) for the public and MedPage (7) for physicians.